Dynamic changes in seed nutritional components of mung bean [(Vigna radiata (L.) R. Wilczek)] under heat stress - Uday Chand Jha; Sadiah Shafi; Shyam Tallury; Harsh Nayyar; Ashis Ranjan Udgata; Ignacio A. Ciampitti; Kadambot H. M. Siddique; P. V. Vara Prasad (Scientific Reports)
Abstract The increasing challenges of high-temperature (heat stress) significantly impact plant growth and crop yield, including mung bean [(Vigna radiata (L.) R. Wilczek]. Simultaneously, seed quality, encompassing various seed nutrition components, is adversely affected by heat stress. To examine the impact of heat stress, we investigated the seed nutritional profiling of ten selected diverse mung bean genotypes for seed compounds (all expressed in concentration), protein, carbon (C), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and micronutrients, with main focused on seed iron (Fe), zinc (Zn), manganese (Mn), copper (Cu), and sulfur (S), under both control and heat stress conditions. All seed nutrient components, except seed protein, decreased under heat stress relative to the control. Furthermore, to gain insights into the genotype (G) × temperature (T) effect, the combined analysis of variance revealed a significant G × T effect for all assessed traits, except for seed P, Fe and Cu concentrations. Association analysis of seed components revealed a significant and positive correlation between seed P and protein concentrations under heat stress. Likewise, high and significant associations were observed between seed Ca with S and S with P concentrations under heat stress. However, under the control, seed C and protein, Fe and C, and seed yield per plant (SYP) and Zn all exhibited high and significant negative correlations. Under heat stress, positive and significant associations were observed, including seed protein and P, P and Mg, P and Fe, and S and Mg concentrations. Conversely, significant negative associations were observed between seed Cu and Ca, Cu and Mg, and SYP with seed C and P concentrations. Heat stress adversely affected seed nutritional and yield traits in mung bean.